1995
DOI: 10.1007/bf02188753
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse and the chronically mentally ill: A description of dual diagnosis treatment services in a psychiatric hospital

Abstract: Between 20% and 70% of psychiatric patients have a co-occurring substance use disorder and rates of substance abuse among patients with psychotic disorders are especially high. Patients with co-existing psychosis and substance use disorders typically have poorer outcomes than patients diagnosed with either disorder alone. Frequently, treatment services for such dually diagnosed patients are not integrated and organizational barriers may impede the appropriate detection, referral, and treatment of these patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…There is a high prevalence of persons diagnosed with both a psychiatric disability and a chemical dependency in the United States, as evidenced by both epidemiological data and studies of treatment-seekers in substance abuse and mental health programs (Dixon, Haas, Weiden, Sweeney & Frances, 1991;Gawin & Kleber, 1985;Greenfield, Weiss & Tohen, 1995;Hesselbrock, Meyer & Keener, 1985;Kleinman, Miller & Millman, 1990;Marlowe et al, 1995;Mirin, Weiss & Michael, 1988;Rounseville, Anton & Carroll, 1991;Rounseville, Kosten, Weissman & Kleber, 1986;Rounseville, Weissman, Kleber & Wilber, 1982;Weiss et al, 1986). There is also evidence that those with lifetime comorbidity are more likely than those with a single disorder to experience major impairments in economic roles (e.g., unemployment, financial problems) and social roles (e.g., social isolation, interpersonal conflicts; see Kessler, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…There is a high prevalence of persons diagnosed with both a psychiatric disability and a chemical dependency in the United States, as evidenced by both epidemiological data and studies of treatment-seekers in substance abuse and mental health programs (Dixon, Haas, Weiden, Sweeney & Frances, 1991;Gawin & Kleber, 1985;Greenfield, Weiss & Tohen, 1995;Hesselbrock, Meyer & Keener, 1985;Kleinman, Miller & Millman, 1990;Marlowe et al, 1995;Mirin, Weiss & Michael, 1988;Rounseville, Anton & Carroll, 1991;Rounseville, Kosten, Weissman & Kleber, 1986;Rounseville, Weissman, Kleber & Wilber, 1982;Weiss et al, 1986). There is also evidence that those with lifetime comorbidity are more likely than those with a single disorder to experience major impairments in economic roles (e.g., unemployment, financial problems) and social roles (e.g., social isolation, interpersonal conflicts; see Kessler, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Inpatient hospitalization, assessment, crisis intervention, medication management, money management, laboratory screening, housing, and vocational rehabilitation incorporate special features that are tailored specifically for dual diagnosis. For example, hospitalization is considered a component of the system that supports movement toward recovery by providing diagnosis, stabilization, and linkage with outpatient dual diagnosis interventions during acute episodes [47]. Similarly, housing and vocational programs can be used to support the dually diagnosed individual in acquiring skills and supports needed for recovery [48].…”
Section: Critical Componentsmentioning
confidence: 99%
“…Counselors in forensic psychiatric treatment settings typically provide intensive substance abuse treatment to their patients and frequently need to do so as a condition of discharge to a less restrictive environment (Beck, 2002;Ogloff, 2004;Wheatley, 1998). Given the high comorbidity rates (from 15% to 70%) between substance abuse and severe psychiatric disorders (e.g., schizophrenia; Greenfield, Weiss, & Tohen, 1995;Lehman, Myers, Corty, & Thompson, 1994;Soni et al, 2005;Storch, 1992), substance abuse counseling has been demonstrated to be an important and effective intervention for this population (Brower, Blow, & Beresford, 1989;K. B. Carey, Purnine, Maisto, Carey, & Simons, 2000;Cimino, 2002;Kaufman, 1989;Leach, Hardy, & Dinwiddie, 1998;Levy, 2002;Levy & Mann, 1988;Mowbray et al, 1995).…”
mentioning
confidence: 99%